اقبال کے تصورِ ابلیس کا توضیحی مطالعہ: Iqbal’s Concept of Iblees: An explanatory Study - Yasmeen, Sameah (Tashkeel e Jadeed, 2025)
Iqbal was a thoughtful, wise and intelligent person among his contemporaries. After studying philosophy, he not only arrived at rational conclusions but also formulated new meanings and concepts. These concepts are all encompassing his concept of Self. Iqbal`s concept of Iblees is such a concept in which Iqbal presented Iblees a person of continuous struggle, action and unwavering determination. Iblees is not only mixture of evil, Iqbal, has also seen some elements of his character with a favorable eye and preached the Muslims of the today that just like Iblees, man`s intentions should also be unwavering. In this article I have discussed the same thing.